Phylogenetic Relationships Within Chrysogorgia (Alcyonacea: Octocorallia), a Morphologically Diverse Genus of Octocoral, Revealed Using a Target Enrichment Approach - Untiedt, Candice Bobby; Quattrini, Andrea M.; McFadden, Catherine S.; Alderslade, Phil A.; Pante, Eric; Burridge, Christopher P. (Frontiers in Marine Science, 2021)
The octocoral genus Chrysogorgia (Duchassaing and Michelotti, 1864) contains 81 nominal species that are ecologically important components of benthic communities. Taxonomic examination of a large set of samples revealed many provisional new species, exhibiting a wide range of morphological variation. We established nine, distinct morphological groups of Chrysogorgia s.l. that were hypothesized to represent distinct genera. Here, we applied a recently developed universal target enrichment bait method for octocoral exons and ultraconserved elements (UCEs) on 96 specimens varying in morphology, collection ages and DNA quality and quantity to determine whether there was genetic support for these morphologically defined groups. Following Illumina sequencing and SPAdes assembly we recovered 1,682 of 1,700 targeted exon loci and 1,333 of 1,340 targeted UCE loci. Locus recovery per sample was highly variable and significantly correlated with time since specimen collection (2–60 years) and DNA quantity and quality. Phylogenetically informative sites in UCE and exon loci were ∼35% for 50% and 75% taxon-occupancy matrices. Maximum likelihood analyses recovered highly resolved trees with topologies supporting the recognition of 11 candidate genera, corresponding with morphological groups assigned a priori, nine of which are novel. Our results also demonstrate that this target-enrichment approach can be successfully applied to degraded museum specimens of up to 60 years old. This study shows that an integrative approach consisting of molecular and morphological methods will be essential to a proper revision of Chrysogorgia taxonomy and to understand regional diversity of these ecologically important corals.